PENGELOLAAN FASILITAS DI OBJEK WISATA PANTAI TAMAN NIRWANA BUNGUS TELUK KABUNG DI KOTA PADANG - Silitonga, Dahlia Rahmana; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This research aims to describe the management of facilities at the beach tourism object Nirwana Park. The type of research is descriptive qualitative research. The indicator in the research are primary facilities and supporting facilities wich are always from planning, organizing, actuating, and controlling. The research result shows that planning are still done by generally and not detail. Organizing fields are done by the owner of the tourist atraction. Actuating is done by influencing and giving direction in how the employee must do its task in order to create a positif impression for the tourism the attraction. Control is not well done yet, there are to basic standard in meacuring the acrevement of the goal that had been apointed. Keywords: Facilities Management, Tourist Attraction, Beach